The Effect of E-Modules Context-Based on Students Science Communication Skill in Optical Tools and Global Warming - Febrian Syah; Desnita Desnita; Yenni Darvina; Renol Afrizon (Universitas Negeri Padang, 2023)
This research is motivated by the low ability of students' science communication, the cause of the low ability of students' science communication because the teaching materials used by teachers in schools are less effective and quite difficult to understand. This study aims to see the effect the use of context-based physics learning e-modules on optical instruments and global warming for class XI Senior high school. The subjects of this study were all students of class XI Natural Science Mathematics Senior High School. Sampling was carried out using simple random sampling technique, by selecting class XI Natural Science Mathematics 1 as the experimental class and XI Natural Science Mathematics 2 as the control class. The research instrument is a non-test in the form of an observation sheet of scientific communication skills. The data research technique used in hypothesis testing is the t-test. The results showed that the average science communication ability of the experimental class students was higher than that of the control class. The results of testing the assumptions using the t-test, obtained ???? count of 61.10 and ???? table with a significance level of 0.05 with a table value of 1.669. So it can be concluded that there is an effect of the use of context-based physics learning e-modules on students' science communication skills in the material of optical instruments and global warming class XI Senior High School